The Written Self in the Age of Reason - Kaló, Krisztina (Hungarian Journal of English and American Studies, 2020)
Book review:Baker, John, Marion Leclair, and Allan Ingram, eds. Writing and Constructing the Self in Great Britain in the Long Eighteenth Century. Manchester: Manchester UP, 2019. xiii + 288 pages. ISBN 978-1-5261-2336-7. Hb. £80.00.